Challenges in Managing Stakeholders for Quality Education in Primary Schools of Bangladesh: Perspectives from Head Teachers - Haider, Tanami; Kumar Roy , Bijon (Papanda Publisher, 2025)
The present study aims to explore the challenges faced by head teachers in managing various stakeholders including guardians, community people, assistant teachers, and staffs of an educational institution. This study used a qualitative approach to explore the perceptions from head teachers in Khulna region of Bangladesh. The study purposefully selected 15 head teachers with more than 10 years’ experience as participants. Semi-structured questionnaire was followed to take in-depth interview from the participants as the method of data collection. The collected data analyzed thematically to understand the patterns of challenged experienced by the head teacher. This study found headmaster faced challenges from three different types of stakeholders that affects quality education. The study found that head teachers face problems like that guardian not being actively involved, giving conflicting opinions, expecting too much one-to-one attention, spreading false information and creates misunderstandings between guardians and staff. Besides, community people also had a part of it. Community members who were involved in money extortion, misusing school resources, putting political influence on SMC, and comparing with other school activities. Therefore, from the assistant teachers, head teachers faced challenges including internal conflict and groupings among teachers, challenges related to the age gap between assistant teachers and head teachers, extreme involvement in external gossip, and challenges in training distribution. The significant of the study is to design targeted interventions that improve school leadership, management, and educational outcomes in primary schools in Bangladesh.